Consistent, Scale‐Dependent Differences in the Biogeography of Host‐Associated and Free‐Living Microbiomes Across Systems - Joshua H. Dominguez; Andreas Härer; Christopher B. Wall; Diana J. Rennison; Celia C. Symons; Jonathan B. Shurin (Molecular Ecology, 2026)
Microbial communities are critical to the functioning of ecosystems and shape the ecology and evolution of host organisms. However, we have a limited understanding of how host‐associated and free‐living microbes differ in their structure and biogeography. Here, we test whether host‐associated (fish gut) and free‐living (lake bacterioplankton) microbes exhibit different metacommunity structure, spatial turnover, and consistency with neutral expectations using two independent lake systems. We characterized microbial communities in lake water (Vancouver Island and Sierra Nevada) and guts in two fish species (stickleback and brook trout) using 16S amplicon sequencing. We compared alpha and beta diversity within lakes, quantified spatial turnover (distance‐decay), and tested for departure from neutral abundance‐occurrence expectations between bacterioplankton and fish gut microbiomes. Fish microbiomes had lower alpha diversity compared to bacterioplankton, but higher beta diversity within lakes. Bacterioplankton were more similar across lakes yet showed stronger patterns of spatial turnover with distance than fish gut microbiomes. A neutral model explained a substantial proportion of abundance‐occurrence relationships in bacterioplankton communities but performed poorly for fish‐associated microbes. Our study indicates that host‐associated and free‐living microbes have disparate patterns of metacommunity structure and spatial turnover consistent with differences in the strength of neutral ecological processes. Fish microbiomes were less diverse at the local scale but more variable across space and time than bacterioplankton communities, suggestive of potentially strong local selection and/or reduced microbial exchange among hosts compared to environmental communities. Importantly, we observed highly consistent patterns across both lake systems despite differences in host species, sampling design, and region, demonstrating that differences in the distribution of host and environmental microbes are potentially widespread. This study demonstrates how host association fundamentally alters the diversity and spatial distribution of microbes, emphasizing the need to incorporate hosts into broader frameworks of microbial biogeography.

Fire transforms effects of terrestrial subsidies on aquatic ecosystem structure and function - Christopher B. Wall; Cody J. Spiegel; Evelyn M. Diaz; Cindy H. Tran; Alexia Fabiani; Taryn Y. Broe; Elisabet Perez‐Coronel; Sara L. Jackrel; Natalie Mladenov; Celia C. Symons; Jonathan B. Shurin (Global Change Biology, 2024)
Fire can lead to transitions between forest and grassland ecosystems and trigger positive feedbacks to climate warming by releasing CO 2 into the atmosphere. Climate change is projected to increase the prevalence and severity of wildfires. However, fire effects on the fate and impact of terrestrial organic matter (i.e., terrestrial subsidies) in aquatic ecosystems are unclear. Here, we performed a gradient design experiment in freshwater pond mesocosms adding 15 different amounts of burned or unburned plant detritus and tracking the chronology of detritus effects at 10, 31, 59, and 89 days. We show terrestrial subsidies had time‐ and mass‐dependent, non‐linear impacts on ecosystem function that influenced dissolved organic carbon (DOC), ecosystem metabolism (net primary production and respiration), greenhouse gas concentrations (carbon dioxide [CO 2 ], methane [CH 4 ]), and trophic transfer. These impacts were shifted by fire treatment. Burning increased the elemental concentration of detritus (increasing %N, %P, %K), with cascading effects on ecosystem function. Mesocosms receiving burned detritus had lower [DOC] and [CO 2 ] and higher dissolved oxygen (DO) through Day 59. Fire magnified the effects of plant detritus on aquatic ecosystem metabolism by stimulating photosynthesis and respiration at intermediate detritus‐loading through Day 89. The effect of loading on DO was similar for burned and unburned treatments (Day 10); however, burned‐detritus in the highest loading treatments led to sustained hypoxia (through Day 31), and long‐term destabilization of ecosystem metabolism through Day 89. In addition, fire affected trophic transfer by increasing autochthonous nitrogen source utilization and reducing the incorporation of 15 N‐labeled detritus into plankton biomass, thereby reducing the flux of terrestrial subsidies to higher trophic levels. Our results indicate fire chemically transforms plant detritus and alters the role of aquatic ecosystems in processing and storing carbon. Wildfire may therefore induce shifts in ecosystem functions that cross the boundary between aquatic and terrestrial habitats.

Life after a fiery death: Fire and plant biomass loading affect dissolved organic matter in experimental ponds - Cody J. Spiegel; Natalie Mladenov; Christopher B. Wall; Kelly Hollman; Cindy H. Tran; Celia C. Symons; Jonathan B. Shurin (Global Change Biology, 2024)
Drier and hotter conditions linked with anthropogenic climate change can increase wildfire frequency and severity, influencing terrestrial and aquatic carbon cycles at broad spatial and temporal scales. The impacts of wildfire are complex and dependent on several factors that may increase terrestrial deposition and the influx of dissolved organic matter (DOM) from plants into nearby aquatic systems, resulting in the darkening of water color. We tested the effects of plant biomass quantity and its interaction with fire (burned vs. unburned plant biomass) on dissolved organic carbon (DOC) concentration and degradation (biological vs. photochemical) and DOM composition in 400 L freshwater ponds using a gradient experimental design. DOC concentration increased nonlinearly with plant biomass loading in both treatments, with overall higher concentrations (>56 mg/L) in the unburned treatment shortly after plant addition. We also observed nonlinear trends in fluorescence and UV‐visible absorbance spectroscopic indices as a function of fire treatment and plant biomass, such as greater humification and specific UV absorbance at 254 nm (a proxy for aromatic DOM) over time. DOM humification occurred gradually over time with less humification in the burned treatment compared to the unburned treatment. Both burned and unburned biomass released noncolored, low molecular weight carbon compounds that were rapidly consumed by microbes. DOC decomposition exhibited a unimodal relationship with plant biomass, with microbes contributing more to DOC loss than photodegradation at intermediate biomass levels (100–300 g). Our findings demonstrate that the quantity of plant biomass leads to nonlinear responses in the dynamics and composition of DOM in experimental ponds that are altered by fire, indicating how disturbances interactively affect DOM processing and its role in aquatic environments.

Intermittent instability is widespread in plankton communities - Tanya L. Rogers; Stephan B. Munch; Shin‐ichiro S. Matsuzaki; Celia C. Symons (Ecology Letters, 2023)
Chaotic dynamics appear to be prevalent in short‐lived organisms including plankton and may limit long‐term predictability. However, few studies have explored how dynamical stability varies through time, across space and at different taxonomic resolutions. Using plankton time series data from 17 lakes and 4 marine sites, we found seasonal patterns of local instability in many species, that short‐term predictability was related to local instability, and that local instability occurred most often in the spring, associated with periods of high growth. Taxonomic aggregates were more stable and more predictable than finer groupings. Across sites, higher latitude locations had higher Lyapunov exponents and greater seasonality in local instability, but only at coarser taxonomic resolution. Overall, these results suggest that prediction accuracy, sensitivity to change and management efficacy may be greater at certain times of year and that prediction will be more feasible for taxonomic aggregates.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Trophic control changes with season and nutrient loading in lakes - Tanya L. Rogers; Stephan B. Munch; Simon D. Stewart; Eric P. Palkovacs; Alfredo Giron‐Nava; Shin‐ichiro S. Matsuzaki; Celia C. Symons (Ecology Letters, 2020)
Experiments have revealed much about top‐down and bottom‐up control in ecosystems, but manipulative experiments are limited in spatial and temporal scale. To obtain a more nuanced understanding of trophic control over large scales, we explored long‐term time‐series data from 13 globally distributed lakes and used empirical dynamic modelling to quantify interaction strengths between zooplankton and phytoplankton over time within and across lakes. Across all lakes, top‐down effects were associated with nutrients, switching from negative in mesotrophic lakes to positive in oligotrophic lakes. This result suggests that zooplankton nutrient recycling exceeds grazing pressure in nutrient‐limited systems. Within individual lakes, results were consistent with a ‘seasonal reset’ hypothesis in which top‐down and bottom‐up interactions varied seasonally and were both strongest at the beginning of the growing season. Thus, trophic control is not static, but varies with abiotic conditions – dynamics that only become evident when observing changes over large spatial and temporal scales.

Sierra Nevada mountain lake microbial communities are structured by temperature, resources and geographic location - Marika A. Schulhof; Andrew E. Allen; Eric E. Allen; Natalie Mladenov; John P. McCrow; Natalie T. Jones; Jessica Blanton; Hamanda B. Cavalheri; Drishti Kaul; Celia C. Symons; Jonathan B. Shurin (Molecular Ecology, 2020)
Warming, eutrophication (nutrient fertilization) and brownification (increased loading of allochthonous organic matter) are three global trends impacting lake ecosystems. However, the independent and synergistic effects of resource addition and warming on autotrophic and heterotrophic microorganisms are largely unknown. In this study, we investigate the independent and interactive effects of temperature, dissolved organic carbon (DOC, both allochthonous and autochthonous) and nitrogen (N) supply, in addition to the effect of spatial variables, on the composition, richness, and evenness of prokaryotic and eukaryotic microbial communities in lakes across elevation and N deposition gradients in the Sierra Nevada mountains of California, USA. We found that both prokaryotic and eukaryotic communities are structured by temperature, terrestrial (allochthonous) DOC and latitude. Prokaryotic communities are also influenced by total and aquatic (autochthonous) DOC, while eukaryotic communities are also structured by nitrate. Additionally, increasing N availability was associated with reduced richness of prokaryotic communities, and both lower richness and evenness of eukaryotes. We did not detect any synergistic or antagonistic effects as there were no interactions among temperature and resource variables. Together, our results suggest that (a) organic and inorganic resources, temperature, and geographic location (based on latitude and longitude) independently influence lake microbial communities; and (b) increasing N supply due to atmospheric N deposition may reduce richness of both prokaryotic and eukaryotic microbes, probably by reducing niche dimensionality. Our study provides insight into abiotic processes structuring microbial communities across environmental gradients and their potential roles in material and energy fluxes within and between ecosystems.

Integrating team science into interdisciplinary graduate education: an exploration of the SESYNC Graduate Pursuit - Kenneth E. Wallen; Karen Filbee-Dexter; Jeremy B. Pittman; Stephen M. Posner; Steven M. Alexander; Chelsie L. Romulo; Drew E. Bennett; Elizabeth C. Clark; Stella J.M. Cousins; Bradford A. Dubik; Margaret Garcia; Heather A. Haig; et al. (Journal of Environmental Studies and Sciences, 2019)

Antagonistic effects of temperature and dissolved organic carbon on fish growth in California mountain lakes - Celia C. Symons; Marika A. Schulhof; Hamanda B. Cavalheri; Jonathan B. Shurin (Oecologia, 2019)

Effects of ocean warming and lowered pH on algal growth and palatability to a grazing gastropod - Alistair G. B. Poore; Sarah E. Graham; Maria Byrne; Symon A. Dworjanyn (Marine Biology, 2016)

Structure and genesis of the Cubango Megafan in northern Namibia: implications for its hydrogeology - F. Lindenmaier; R. Miller; J. Fenner; G. Christelis; H. G. Dill; T. Himmelsbach; S. Kaufhold; C. Lohe; M. Quinger; F. Schildknecht; G. Symons; A. Walzer; et al. (Hydrogeology Journal, 2014)

Direct and indirect effects of ocean acidification and warming on a marine plant–herbivore interaction - Alistair G. B. Poore; Alexia Graba-Landry; Margaux Favret; Hannah Sheppard Brennand; Maria Byrne; Symon A. Dworjanyn (Oecologia, 2013)

Role of Brassinosteroids, Ethylene, Abscisic Acid, and Indole-3-Acetic Acid in Mango Fruit Ripening - Sakimin S. Zaharah; Zora Singh; Gregory M. Symons; James B. Reid (Journal of Plant Growth Regulation, 2012)

Infection rate and colonization with antibiotic-resistant organisms in skilled nursing facility residents with indwelling devices - L. Wang; B. Lansing; K. Symons; E. L. Flannery; J. Fisch; K. Cherian; S. E. McNamara; L. Mody (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

The hormonal regulation of de-etiolation - Gregory M. Symons; Jennifer J. Smith; Takahito Nomura; Noel W. Davies; Takao Yokota; James B. Reid (Planta, 2008)

Evidence that the mature leaves contribute auxin to the immature tissues of pea (Pisum sativum L.) - Corinne E. Jager; Gregory M. Symons; Naomi E. Glancy; James B. Reid; John J. Ross (Planta, 2007)

The brassinosteroid growth response in pea is not mediated by changes in gibberellin content - Corinne E. Jager; Gregory M. Symons; John J. Ross; Jennifer J. Smith; James B. Reid (Planta, 2005)

Interactions Between Light and Plant Hormones During De-etiolation - Gregory M. Symons; James B. Reid (Journal of Plant Growth Regulation, 2003)

Hormone levels and response during de-etiolation in pea - Gregory M. Symons; James B. Reid (Planta, 2003)

Auxin-Gibberellin Interactions and Their Role in Plant Growth - John J. Ross; Damian P. O'Neill; Carla M. Wolbang; Gregory M. Symons; James B. Reid (Journal of Plant Growth Regulation, 2001)

Paleomagnetism of the Society Cliffs dolostone and the age of the Nanisivik zinc deposits, Baffin Island, Canada - D. T. A. Symons; T. B. Symons; D. F. Sangster (Mineralium Deposita, 2000)

Phylogenetic indices for measuring the diet breadths of phytophagous insects - Fernley B. Symons; George W. Beccaloni (Oecologia, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)